2021
DOI: 10.25251/skin.5.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Offering Pneumococcal Vaccines During Specialty Care on Vaccination Rates in Patients Receiving Immunosuppressive

Abstract: Purpose: To determine whether clinician-led immunization education with immediate onsite vaccination availability will increase pneumococcal immunizations during specialty care. Methods: We designed a controlled before and after QI project quasi-experimental design to retrospectively evaluate the QI effectiveness. The QI setting included two clinics. Clinic #1 was a part of the county hospital system and offered comprehensive care. Clinic #2 was a university clinic that hosted a private practice and a dermatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Consistent with our finding of lacking physician’s vaccination recommendation being a major determinant of negative vaccination status, Lindsley et al [ 29 ] concluded that vaccination recommendation resulted in increased vaccination rates in patients treated with immunosuppressants due to a dermatological condition. This effect was also identified in other patient populations, for example in diabetic and cardiology patients, indicating that awareness about the beneficial aspects of vaccination brought forward by physicians proves to have a positive influence on vaccination status [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our finding of lacking physician’s vaccination recommendation being a major determinant of negative vaccination status, Lindsley et al [ 29 ] concluded that vaccination recommendation resulted in increased vaccination rates in patients treated with immunosuppressants due to a dermatological condition. This effect was also identified in other patient populations, for example in diabetic and cardiology patients, indicating that awareness about the beneficial aspects of vaccination brought forward by physicians proves to have a positive influence on vaccination status [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 91%